Pruebas a equipos de protección contra sobretensiones en subestaciones eléctricas, dps (2021)
The purpose of the degree work is to design the protocols that are applied in a substation to carry out the necessary tests to DPS, which can be carried out at start-up or to verify the current operating status. The protocols establish the procedures and analyzes on how the necessary tests should be carried out on disconnectors in electrical substations, in accordance with international and national standards and recommendations given by the manufacturer.